2021
DOI: 10.3390/ijerph18179182
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Maternal Factors on Problematic Smartphone Use among Elementary School Children

Abstract: Mothers play a key role in ensuring their children’s healthy life. This study aimed to identify the maternal factors affecting problematic smartphone use in children. We adopted a cross-sectional descriptive design using structured questionnaires. Participants were fourth to sixth grade elementary school students in Korea (n = 184). The following maternal factors were evaluated: maternal mediation, children’s perception of mothers’ smartphone use, mother–child communication, and parenting style. Data regarding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
(61 reference statements)
0
8
0
Order By: Relevance
“…A study by Yao et al (2021) explained that adolescents' need for frustration and problematic smartphone use was determined by parental psychological control. Another possible explanation for our finding is that adolescents might increase the use of smartphones to satisfy their unmet basic psychological needs (Lee & Kim, 2021). Adolescents will perceive parental psychological control as a stressful situation and use smartphones as dysfunctional coping stress (Li et al, 2013;Wu et al, 2016).…”
Section: Discussionmentioning
confidence: 93%
“…A study by Yao et al (2021) explained that adolescents' need for frustration and problematic smartphone use was determined by parental psychological control. Another possible explanation for our finding is that adolescents might increase the use of smartphones to satisfy their unmet basic psychological needs (Lee & Kim, 2021). Adolescents will perceive parental psychological control as a stressful situation and use smartphones as dysfunctional coping stress (Li et al, 2013;Wu et al, 2016).…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, studies that examine parental smartphone mediation in relation to problematic smartphone use in children (10 years old and below) have shown that active and restrictive mediation served as a protective factor against problematic smartphone use [ 15 , 16 ]. In contrast, other studies have found that active and restrictive maternal mediation did not affect children’s (10 to 12 years old) problematic smartphone use [ 17 ], and that restrictive mediation may even increase its likelihood in children and adolescents aged 10 to 18 years old [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 92%
“…Nielson et al [ 32 ] conducted a systematic literature review on adolescents aged 12 to 19 years old and found that none of the three parental mediation strategies—active, restrictive, or co-viewing—were consistently associated with an increase or decrease in problematic internet use and problematic online gaming. Similarly, Lee et al [ 17 ] found that parental mediation—specifically, that of mothers—had no significant effect on children’s (10 to 12 years old) problematic smartphone use. Recently, however, Yang et al [ 33 ] studied children aged 10 to 12 years and found that the use of active mediation significantly predicted less problematic smartphone use in children.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it was also pointed out that instead of screen time, the type of content/media and purpose of use has a more significant impact on addiction (Hong, 2022;Lee and Kim, 2021a;Oh et al, 2020;Song, 2022). Internal factors such as children's temperamental/risk type (Hong, 2022;Kim, 2022;Song, 2022), psychological aspect which includes emotional stability (Hong, 2022;Kim and Jahng, 2021;Kim and Kang, 2022;Kim, 2022;Lee and Mun, 2022), playfulness (Kim and Kang, 2022), self-esteem (Lee and Kim, 2021b;Kim and Park, 2021), and mental health (Jeong et al, 2019;Kim, 2022;Lee and Mun, 2022) were associated with how they interact with and are affected by digital interaction. Meanwhile, external factors such as economy , peer relationships (Ju, 2019;Kim and Kang, 2022), and COVID-19 were also contributing factors which affect children's interaction with digital devices indirectly, impacting their DW.…”
Section: Causes/factors That Affect Digital Wellbeingmentioning
confidence: 99%